Javanese Culture in Maternal Postpartum Care at Hargomulyo Village, Kedewan District, Bojonegoro Regency - Devi Endah Saraswati (Jurnal Ilmiah Kesehatan, 2021)
Maternal and child health problems are inseparable from socio-cultural andenvironmental factors in society. Factors of belief and traditional knowledgepositively or negatively impact Maternal and Child Health (MCH). Culturecould be a predisposing factor for high maternal mortality. This paperdescribes Javanese culture in maternal postpartum care at HargomulyoVillage, Kedewan District, Bojonegoro Regency. This study was descriptiveresearch. It took place at Hargomulyo Village, Kedewan District, BojonegoroRegency, from January to February 2020. The population was mothers whohave experienced postpartum both primipara and multipara. There were 48respondents by total sampling. The instrument used a questionnaire consistingof several questions regarding culture in maternal postpartum care, how tocarry out the culture, and its reasons. Thirty respondents did food taboos(62.5%), six respondents limited their drinking water (12.5%), 40 respondentsdrank herbs (83.3%), 47 respondents wore stagen (97.9%), and fiverespondents used pilis (10.4%). In addition, 48 respondents performedbrokohan and mendem ari ari (100%), 20 respondents were not allowed totake a nap (41.7%), and 18 respondents must be at home for 40 days (37.5%).At the same time, 17 respondents did perineal care after birth with betel leaf(35.4%), 12 respondents walked and sat with feet parallel (25%), and 20respondents did semi-sitting position (41.7%). Postpartum mothers stillpractice many Javanese cultures. This culture has both favorable andunfavorable impacts on health. Furthermore, it is necessary to analyze theinfluence of Javanese culture on the health status of postpartum mothers.